Development of Financial Engineering: An Economics Perspective - Chaudhuri, Dr. Ranjan (Indian Journal of Finance, 2007)
This article deals with a broad array of topics that fit together through certain logic that we generally call Financial Engineering. The approach uses a combination of historical anecdotes, elementary discussion on mathematics for Finance and Economics and real world examples. This article have attempted to connect the three distinct but interdependent fields of study, namely, Economics, Econometrics and Financial Engineering, their conception and their use in economic planning. It combines technical and conceptual advances from various disciplines to create a broad interdisciplinary body of knowledge, ready to meet the challenges of a rapidly growing market and an exciting future.